Dielectric aging behavior in A-site hybrid-doped BaTiO3 ceramics - Sareein T. (2014)
Hybrid-doped ferroelectric ceramics have recently been of great interest. Their electrical properties; however, remained mysterious, particularly the aging behavior. Therefore, the dielectric aging characteristics of the A-site hybrid-doped Na1+/Sm3+ BaTiO3 perovskite ceramics were investigated in this study. With the concentration of acceptor dopant (Na1+) fixed at 1 mol%, while that of the donor dopant (Sm3+) varied from 0.0 to 1.5 mol%, the hybrid-doped BaTiO 3 ceramics were prepared successfully by a conventional mixed-oxide method via vibro-milling technique. The results showed that the dielectric properties of all de-aged samples decreased noticeably with time. In all the samples with 0.5, 1.0 and 1.5 mol% Sm3+ obviously the aging of dielectric constant and dielectric loss did not follow the conventional logarithmic law. The stretched exponential decay was found to suitably represent the aging behavior of these A-site hybrid-doped BaTiO3 ceramics. A possibly cause of such behavior lies in the nature of relaxor-like behavior of these ceramics induced from a disruption of dipole ordering from Na 1+/Sm3+ substitution. © 2011 Elsevier B.V. All rights reserved.